Manajemen Sarana dan Prasarana SMP dan SMA Pesantren Modern dalam Menghadapi Era Revolusi Industri 4.0 (Studi Deskriptif di SMP dan SMA Pesantren Modern Daar El Falaah Kecamatan Mandalawangi Kabupaten Pandeglang Banten) - Setia Winata (Journal on Education, 2023)
The background of the problem in this study is that the management of facilities and infrastructure has not been implemented in accordance with the current educational revolution and the lack of facilities and infrastructure at Islamic boarding schools. The purpose of this research is to describe, understand, and analyze (1) Modern Islamic Boarding School Facility and Infrastructure Management in facing the industrial revolution 4.0 era at Daar El Falaah Mandalawangi Modern Islamic Boarding School, Pandeglang Regency (2) To find out the planning, inventory and maintenance of Facilities Management and Infrastructure of Modern Islamic Boarding Schools in facing the era of the industrial revolution 4.0 at Daar El Falaah Mandalawangi Modern Islamic Boarding School, Pandeglang Regency. This study uses a qualitative method with a descriptive approach. The results of the research are the collection of data on facilities and infrastructure by the foundation's facility and infrastructure supervisor, coding of goods, classification of goods, and administration. As for the maintenance of the pesantren facilities, it is the responsibility of each person in charge of the room and homeroom teacher, and the maintenance of the pesantren infrastructure is the responsibility of the supervisor of facilities and infrastructure with regular checking efforts once a year to prevent damage. Furthermore, the elimination of facilities and infrastructure is determined by the daily chief executive in coordination with the foundation treasurer. The elimination step is the sale of damaged goods by weighing and the sale of used goods for usable goods that are no longer used. From the conclusions that have been obtained, the authors can conclude that the management of the facilities and infrastructure of the modern Islamic boarding school Daar el Falaah is not ready to face the era of the industrial revolution 4.0 due to time constraints, costs and only a few educators who can master technology.